PENINGKATAN KAPASITAS MANAJEMEN ORGANISASI DAN KEUANGAN PETANI MELON DI SALAM MAGELANG - Puspitasari, Etika Dyah; Febrianti, Novi; Yudhana, Anton (Jurnal Abdi Insani, 2026)
The “Rukun Tani” Melon Farmers Group in Baturono Village, Salam District, Magelang Regency possesses strong potential for developing melon cultivation. However, as a newly established group, they still face several challenges, particularly in organizational management and financial administration. This community service program aimed to enhance the managerial capacity of the farmers through targeted training and mentoring activities. The program was implemented from June to October 2025 through several stages, including: (1) preparation, which consisted of needs assessment and development of training materials; (2) interactive training sessions on organizational and financial management; (3) mentoring in the implementation of organizational structures and financial record-keeping; and (4) evaluation using pretest and posttest instruments. Data obtained from the evaluations were analyzed using quantitative descriptive methods to assess improvements in participants’ understanding, measured by the difference between pretest and posttest scores. The results showed that participants’ understanding of organizational management increased by 23.10%, while their understanding of financial management improved by 23.57%. These findings indicate that the training and mentoring activities significantly contributed to strengthening the managerial skills of the group members. Overall, the program proved effective in enhancing the institutional capacity of the Rukun Tani Melon Farmers Group and is expected to promote more professional and sustainable organizational management to support the development of melon cultivation in Baturono Village.